Phenotypic diversity in beta-HbE thalassemia patients - Pustika Amalia Wahidiyat; Djajadiman Gatot; Tenny Tjitrasari; Harapan Parlindungan Ringoringo; N S Marzuki; R A Taufani; I Setianingsih; A Harahap (Indonesian Pediatric Society Publishing House, 2016)
Background Thalassemia is a monogenic disease, yet the clini- cal manifestations (phenotype) are variable although they have the same genotype. The clear-cut correlation between genotype and phenotype in β-thalassaemia/HbE patients remains unex- plained. There are several factors that play a role in the severity of the clinical manifestations, i.e. two alpha-gene deletion, homozy- gote Xmn1 polymorphism +/+, -+-++, ++-++ haplotype, and hemo- globin Constant Spring. Objective To understand the clinical diversity of patients with HbE/ α thalassemia and to determine whether it is possible to predict phenotypic severity from genetic factors. Methods A descriptive study on clinical presentations and hema- tological data of beta-HbE thalassemia patients. DNA analysis was performed to detect β-thalassemia mutations and the ameliorating factors (alpha-globin genes deletions and Xmn1 restriction site poly- morphism at position -158 upstream of the G γ-globin gene) which were already known. Results Thirty patients with HbE/β thalassemia (4 to 29 years old) were recruited. IVS1-nt5 (G>C) severe β + mutation was detected in 20 patients. Eighteen of 20 patients with positive IVS1-nt5 mu- tation group were heterozygous for Xmn1 restriction site polymor- phism and none of the patients was co-inherited with two á-globin gene deletion. Almost all patients (19/20) with positive IVS1-nt5 mutation group required regular transfusions, yet the mean age at first blood transfusion was older in negative IVS1-nt5 mutation group than that of positive IVS1-nt5 mutation group (5.7 vs 4 years). Mean hemoglobin before initial transfusion was higher in negative IVS1- nt5 mutation group than that of positive IVS1-nt5 mutation group (5.88 vs 5.39 g/dl). The mean total transfusion per year was lower in the negative IVS1-nt5 mutation group than that of positive IVS1- nt5 mutation group (190.6 vs 215.1 ml/year). Conclusions Beta-HbE thalassemia patients with identical beta thalassemia mutation (IVS1-nt5) show remarkable clinical diver- sity. Neither two alpha-gene deletion, nor the Xmn1- G γ polymor- phism can explain the phenotypic variation. Other ameliorating determinants or genetic modifications responsible for the variable clinical severity remain to be explored.